2016
DOI: 10.7554/elife.15477
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Notch signaling antagonizes PRC2-mediated silencing to promote reprograming of germ cells into neurons

Abstract: Cell-fate reprograming is at the heart of development, yet very little is known about the molecular mechanisms promoting or inhibiting reprograming in intact organisms. In the C. elegans germline, reprograming germ cells into somatic cells requires chromatin perturbation. Here, we describe that such reprograming is facilitated by GLP-1/Notch signaling pathway. This is surprising, since this pathway is best known for maintaining undifferentiated germline stem cells/ progenitors. Through a combination of genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 72 publications
(100 reference statements)
2
58
0
Order By: Relevance
“…How is PRC2 recruited to the Notch ternary complex? Mechanisms for the recruitment of PRC2 to transcription factors remain elusive, but several models have been proposed (4347). Jaird2 has been shown to link PRC2 to chromatin in ES cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…How is PRC2 recruited to the Notch ternary complex? Mechanisms for the recruitment of PRC2 to transcription factors remain elusive, but several models have been proposed (4347). Jaird2 has been shown to link PRC2 to chromatin in ES cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while Notch is required for induction of Y cell fate, it is dispensable for the transition to neuronal cell fate. This Notch functionality may be analogous to the role of Notch signaling in germ cell conversion by antagonizing the repressive heterochromatin state established by PRC2 through expression of histone demethylases . Notch signaling may similarly establish a “memory state” in the Y cell which later permits the Y cell to lose its differentiated identity and gain plasticity (unipotential in this case).…”
Section: Commitment To Unipotency: Naturally Occurring Reprogrammingmentioning
confidence: 93%
“…Analysis of differential gene expression in GLP‐1/Notch loss‐of‐function and gain‐of‐function mutants suggests that Notch permits cell fate conversion by opposing PRC2 action. One identified focal point in this antagonistic relationship is UTX‐1, a JmjC domain‐containing H3K27me3 demethylase; PRC2 silences utx‐1 expression, while Notch signaling activates its expression . utx‐1 transcription is critical for Notch‐enhanced germ cell conversion, and therefore, UTX‐1 may be stimulated to promote reprogramming in the germ cell context.…”
Section: Totipotency To Commitment: Reprogramming In the Germlinementioning
confidence: 99%
“…In the adult germline, PRC2 buffers germ cells against reprogramming: forced expression of a master regulatory protein in the absence of PRC2 components leads to conversion of germ cells into somatic cell types (Patel et al, 2012). Increased GLP-1/Notch signaling in the germline antagonizes PRC2-mediated silencing of somatic genes to promote reprogramming (Seelk et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Expression profiling of germlines lacking P-granule components, PRC2 or MES-4 (Gaydos et al 2012;Knutson et al 2017;Campbell and Updike 2015), or undergoing forced reprogramming in the context of increased GLP-1/Notch signaling (Seelk et al 2016), has shown that loss of germ-cell identity is associated with expression of somatic genes. However, these approaches could not distinguish between genes whose misexpression causes versus is a consequence of a perturbed germline transcriptional program and sterility.…”
Section: Introductionmentioning
confidence: 99%